2013
DOI: 10.1002/eji.201243101
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary arms race between NK cells and viruses: Who gets the short end of the stick?

Abstract: NK cells in viral infectionsNK cells are innate cytotoxic lymphocytes essential for the control of a broad range of viral infections. The activation and function of NK cells are based on a tightly regulated interplay between inhibitory and activating signals induced by the receptors expressed on their surface (reviewed in [1]) or by a variety of cytokines generated by the interaction between NK cells and other innate immune cells, such as macrophages and DCs [2,3]. Type I IFNs, IL-12, IL-15, and IL-18 produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 102 publications
(139 reference statements)
1
31
0
Order By: Relevance
“…The results presented in the present study were supported by additional works demonstrating that Ncr1 indeed plays no role in MCMV infection (36) and in decidual human NK recognition of human CMV (44).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results presented in the present study were supported by additional works demonstrating that Ncr1 indeed plays no role in MCMV infection (36) and in decidual human NK recognition of human CMV (44).…”
Section: Discussionsupporting
confidence: 86%
“…1C). We selected these three strains because past work using depleting Abs against NK cells demonstrated that NK cell function was critical for controlling MCMV infection in all three strains (34)(35)(36)(37).…”
Section: Control Of MCMV Infection Is Not Dependent On Ncr1mentioning
confidence: 99%
“…NK cells are large, granular lymphocytes of the innate immune system that contribute to successful immune responses by killing virally infected or transformed cells and by producing various cytokines [1][2][3]. The function of NK cells is controlled by the integration of signals from activating and inhibitory surface receptors Membrane microdomains, also called lipid rafts, are defined as cholesterol-and sphingolipid-rich membrane domains that affect various cellular functions, such as signaling, protein sorting, or endocytosis [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…However, either interfering with the association between NKG2D and DAP10, or mutating the transmembrane region of 2B4 impacted the recruitment of the receptors to detergentresistant membrane fractions and modulated the function of 2B4 in NK cells. Our data suggest a potential interaction between the transmembrane region of NK-cell receptors and membrane lipids as a molecular mechanism involved in determining the membrane confinement of activating NK-cell receptors.Keywords: 2B4 r Activating receptor r Lipid rafts r Membrane microdomains r NK cells r NKG2D r Signal transduction Additional supporting information may be found in the online version of this article at the publisher's web-site Introduction NK cells are large, granular lymphocytes of the innate immune system that contribute to successful immune responses by killing virally infected or transformed cells and by producing various cytokines [1][2][3]. The function of NK cells is controlled by the integration of signals from activating and inhibitory surface receptors Correspondence: Prof. Carsten Watzl e-mail: watzl@ifado.de [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation